Osteology of the long-whiskered catfish Iheringichthys labrosus Lütken, 1874 (Siluriformes, Pimelodidae) from the upper Paraná River basin, southern Brazil - Shibatta, Oscar Akio; Filho, Hugo Sum De Souza (Zootaxa, 2025)
Iheringichthys labrosus is a catfish from the Paraná River basin with a peculiar conical snout, small mouth, thin premaxillary dentigerous plate, and broad upper lip folded posteriorly, differing from other genera of the Pimelodidae except for the monotypic Bergiaria. This comprehensive study on cleared and stained specimens and dry skeletons of Iheringichthys labrosus demonstrates many similarities with Pimelodus maculatus, showing a conservative skeleton with differences only in the shape of buccal apparatus bones. Bergiaria westermanni diverges from I. labrosus only by a reduced premaxilla and loss of teeth, suggesting autapomorphies of the species and casting doubt on the validity of the genus. Conorhynchos conirostris also has a conical snout and small mouth but does not share several synapomorphies of the Pimelodus-Callophysus group observed in I. labrosus.